FCE Result. Revised: Student's Book - Davies P. A. Paul A. (New York, Oxford University Press, 2011)
Inspires students to better results at FCE. With its contemporary design and up-to-date material, plus interactive test practice, FCE Result gives you total support for the FCE exam. - Vibrant design with high-impact visuals keeps motivation high- Workbook Resource Pack MultiROM provides access to two interactive online FCE practice tests- Integrated dictionary skills work teaches skills for independent learning